A new species of the deep-sea spongicolid genus Spongicoloides (Crustacea, Decapoda, Stenopodidea) and a new species of the glass sponge genus Corbitella (Hexactinellida, Lyssacinosida, Euplectellidae) from a seamount near the Mariana Trench, with a novel commensal relationship between the two genera. (May 2018) - Kou, Qi; Gong, Lin; Li, Xinzheng
Abstract: A new species of the deep-sea spongicolid genus Spongicoloides Hansen, 1908 and a new species of the euplectellid genus Corbitella Gray, 1867 are described and illustrated based on the material recently collected by the remotely operated vehicle 'Faxian' at a seamount near the Mariana Trench. The new deep-sea spongicolid species can be distinguished from the congeneric species by a series of morphological features and the validity of the new species was supported by the molecular phylogenetic analysis. By means of the microscleres of regular hexasters and onychohexasters, the new sponge species can easily be distinguished from other Corbitella species. The new euplectellid sponge species is the host of the new spongicolid shrimp species: this is the first discovery of an association between Spongicoloides and Corbitella . The present study increases the species diversity of both genera as well as yielding new insight into the commensal relationships between spongicolid shrimps and their sponge hosts. Highlights: A new deep-sea spongicolid shrimp of the genus Spongicoloides is described. A new deep-sea glass sponge of the genus Corbitella is described. A novel commensal relationship between spongicolid shrimps and sponges is reported. Host diversity of Spongicoloides may be higher than we thought.